The Psychological Literacy in Arranging Intrapersonal Communication Resolution in Gambling Acts - Sasongko, Probo (LPPM Universitas Jambi, 2025)
The Indonesian nation is experiencing an emergency regarding gambling. The significant impact of gambling affects all aspects. Not only the destruction of family relationships, the loss of material and even a person's life can be a dangerous threat from the game that is forbidden by religion. Various policies and regulations are made to overcome the high level of gambling. Starting from punishment, to a fine that is not small. However, it seems that this does not reduce the number of players to stop gambling. So, from this we need to look deeply, that this gambling game is generally carried out by those who do not have the ability to see carefully about the existence of awareness. The study uses a qualitative method with a critical approach through netnographic studies with reference to the theory of transformation of consciousness developed by Reza Antonius Wattimena. Through this theory, we can see thoroughly that the existence of awareness that is known deeply can be an important key to being able to recognize everything we are facing, including efforts to resolve it. The process of recognizing and understanding what is experienced by each individual through the theory of consciousness will bring the individual to have good skills, related to the phenomenon of the Level of consciousness that is studied in depth, starting from the level of distinctive consciousness to the level of consciousness of emptiness. These levels of awareness will bring each individual to a complex and integrated understanding of gambling. The purpose of this study is broadly oriented to provide a comprehensive understanding that the key to human action is awareness. So, by having good and high awareness we can see and overcome all the dynamics of life in society, especially related to the issue of immoral acts.